Mapping the trends of the family institution: a comparative literature review - Kamaruddin, Zaleha; A. Kadir, Nadhilah; Mohd, Azizah (IIUM Press, 2020)
The article reviews relevant literature to track changes in the family institution by utilizing a comparative approach between Western and Muslim families. The purpose of this method is to map trends in the last five decades and to identify gaps, if any, between the two modern-day family institutions. The article in its introduction, reviews literature that emphasizes on the significance of the family institution as the nucleus of civilization. The second part of the article continues with a review of important works that focus on the challenges in postmodern family life. The main question is whether the family institutions in the Western and Muslim worlds respond differently when faced with the same challenges. The third part of the paper concludes with solution-based familism literature from both jurisdictions that concentrates on empowerment of family institutions. Drawing on these relevant literatures, we find that despite all these changes, values remain an important constant in stabilizing the family institution.